Ibero-American Amerindians: access to health and media in times of COVID-19 pandemic - Ysnel, Estelle (2021)
In this research, I will study the international and constitutional provisions specific to Amerindian people, located in the countries of the ancient Inca Empire and Amazon region. In the time of the Incas, the Arawak, the Taino and the Caribs, it was impossible to separate health, science and knowledge from religion. Communication played an important role. With the Conquest and colonial times, there were transmissions of diseases between the New and Old World. The first legislation on behalf of Indians was already concerned with health and communication. Nowadays, international standards and constitutions give Amerindians the right to access to health, especially physical and mental health. To guarantee this right, their medicine, traditional knowledge from their ancestors, science and technologies are fully recognized. Clearly, this implies the respect of the intellectual property of all this knowledge. Amerindians have also the right to create, to use their own media, as well as to get access to any other media. With COVID-19 pandemic, does media help to broadcast information to fight the pandemic? How is it possible to bring into line treatments against COVID-19 with traditional medicine, practices and knowledge?